Electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber

By adopting a double-layer aluminum trioxide/titanium dioxide film structure on single-crystal organometallic perovskite fibers, the high-efficiency light field interaction between single-layer graphene and optical fiber is achieved, the problem of low light absorption is solved, and the development of high-performance fiber devices is achieved.

CN119681767AActive Publication Date: 2025-03-25GUANGDONG POLYTECHNIC NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411670188.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high-efficiency light field interaction between single-layer graphene and single-crystal organometallic perovskite fiber, resulting in low light absorption and making it difficult to realize high-performance fiber devices.

Method used

The double-layer aluminum trioxide (Al2O3)/titanium dioxide (TiO2) double-layer film structure with a refractive index increased in sequence is used to polish the single-crystal organometallic perovskite fiber on the side to achieve efficient interaction between the optical fiber mode and the single-layer graphene, and the local enhancement effect of the electromagnetic field at the graphene is controlled by controlling the thickness of the double-layer film.

Benefits of technology

The light absorption coefficient of single-layer graphene is significantly improved, and the efficient coupling of optical fiber mode and two-dimensional materials is achieved, providing high-sensitivity fiber humidity sensing and photoelectric detection capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119681767A_ABST
    Figure CN119681767A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic field local enhancement structure based on a double-layer film and a side-polished perovskite optical fiber. The electromagnetic field local enhancement structure comprises a side-polished single-crystal organic metal perovskite optical fiber, a single-layer graphene film, an aluminum oxide film and a titanium dioxide film, the single-layer graphene thin film, the aluminum oxide thin film and the titanium dioxide thin film are arranged above the polishing and grinding surface of the side edge polishing and grinding single crystal organic metal perovskite optical fiber layer by layer; based on a double-layer film structure formed by an aluminum oxide thin film and a titanium dioxide thin film of which the refractive indexes are sequentially increased, interaction between an optical fiber mode and single-layer graphene in the side-polishing single-crystal organic metal perovskite optical fiber is completed, and local enhancement of an electromagnetic field at the graphene is realized; the local enhancement effect of the electromagnetic field at the graphene is regulated and controlled by controlling the double-layer film thickness of the aluminum oxide film and the titanium dioxide film deposited on the side-polished single-crystal organic metal perovskite optical fiber transferred with the single-layer graphene. According to the invention, efficient interaction between a transmission light field and a two-dimensional material in the fiber core can be realized, and a thought is provided for integrating a high-performance photoelectric detector, a sensor and a nonlinear device on the perovskite optical fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical fiber integrated devices and electromagnetic field local enhancement microstructures, and in particular to an electromagnetic field local enhancement structure based on a double-layer film and side-polished perovskite optical fiber. Background Art

[0002] In recent years, the integration of two-dimensional materials and fiber devices has become a research hotspot in the intersection of materials science and micro-nano optoelectronics. Thanks to the excellent optoelectronic and mechanical properties of two-dimensional materials, two-dimensional materials can be integrated with various types of optical fibers and the application scenarios of fiber devices can be expanded to many fields, such as: fiber photodetectors, fiber modulators, fiber sensors, fiber nonlinear devices, etc. The efficient coupling of fiber modes and two-dimensional materials is the prerequisite for realizing high-performance fiber devices.

[0003] Graphene has attracted extensive attention from researchers due to its excellent optical properties, high carrier mobility and high thermal conductivity. However, due to the ultra-small size and atomic layer thickness of single-layer graphene, the light absorption area of ​​single-layer graphene is small and the light absorption rate is low (2.3%), which makes the interaction between light and single-layer graphene face huge challenges. At present, an effective solution is to use resonance effect, metal reflection or combination with waveguide, such as a fiber-optic integrated photodetector with polarization function with patent publication number CN113865702A, which increases light absorption by extending the interaction distance between light and graphene. However, the core diameter of ordinary single-mode optical fiber is only 8μm, so a millimeter-level action distance is usually required to increase the effective interaction area.

[0004] Single-crystal organic metal perovskite has the advantages of high stability, low optical transmission loss, long carrier lifetime, good third-order nonlinear optical properties, etc., making it an ideal material for preparing semiconductor core optical fibers. At present, a variety of methods for preparing single-crystal organic metal perovskite optical fibers have been reported, such as: cooling crystallization method, anti-solvent vapor assisted crystallization method, liquid diffusion separation induced crystallization method and inverse temperature crystallization method. The core of this single-crystal organic metal perovskite optical fiber is a single-crystal organic metal perovskite, and the cladding is silica or tetrafluoroethylene, showing a low transmission loss of <0.7dB / cm, and the diameter of the core reaches hundreds of microns (Zhou Y, Parkes MA, Zhang J, et al. Single-crystal organometallic perovskite optical fibers [J]. Science Advances, 2022, 8 (38): eabq8629.). The large core diameter is conducive to increasing the interaction area between light and matter and reducing the difficulty of optical fiber integration, making it an ideal advanced functional optical fiber platform for preparing light sources, detectors, sensors, and nonlinear optical devices. According to the total reflection transmission principle of optical fiber, light is always transmitted in the core with high refractive index, while the cladding with lower refractive index constrains the light. Before polishing, single-crystal organic metal perovskite optical fiber meets the total reflection condition, and light is transmitted in the single-crystal organic metal perovskite core with high refractive index. After polishing, the silica cladding on one side is removed to expose the core to the air, so that the evanescent field of the optical fiber can leak from the polished surface and interact with the external environment. By covering the polished surface of the optical fiber with different functional materials, detection, sensing and other functions can be achieved. At present, the integration technology of single-crystal organic metal perovskite optical fiber and two-dimensional materials has not been studied, and the refractive index of single-crystal organic metal perovskite (n = 1.9841, @ 1600nm) is much larger than the refractive index of two-dimensional materials such as graphene and molybdenum disulfide. How to achieve efficient interaction between the light field transmitted in the core and the two-dimensional material is a challenge to realize high-performance perovskite optical fiber devices. Summary of the invention

[0005] In order to overcome the defects and shortcomings of the prior art, the present invention provides a local electromagnetic field enhancement structure based on a double-layer film and a side-polished perovskite optical fiber. The present invention utilizes an aluminum oxide (Al2O3) / titanium dioxide (TiO2) double-layer film structure with successively increasing refractive indices to realize a method for efficient interaction between an optical fiber mode and a single-layer graphene in a side-polished single-crystalline organic metal perovskite optical fiber, thereby realizing local enhancement of the electromagnetic field at the graphene. By controlling the thickness of the aluminum oxide (Al2O3) / titanium dioxide (TiO2) double-layer film deposited on the side-polished single-crystalline organic metal perovskite optical fiber to which a single-layer graphene is transferred, the local enhancement effect of the electromagnetic field at the graphene is regulated, thereby providing an effective solution for improving the light absorption coefficient of the single-layer graphene. Titanium dioxide is used as a humidity sensitive material, and the structure provides a supporting basis for realizing highly sensitive optical fiber humidity sensing and photoelectric detection on perovskite optical fibers.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides an electromagnetic field local enhancement structure based on a double-layer film and a side-polished perovskite optical fiber, comprising: a side-polished single-crystal organic metal perovskite optical fiber, a single-layer graphene film, an aluminum oxide film and a titanium dioxide film;

[0008] The single-layer graphene film, the aluminum oxide film and the titanium dioxide film are disposed layer by layer on the polished surface of the side-polished single-crystal organic metal perovskite optical fiber;

[0009] Based on the double-layer film structure composed of aluminum oxide film and titanium dioxide film with increasing refractive index, the interaction between the fiber mode and the single-layer graphene in the side-polished single-crystal organic metal perovskite fiber is realized, and the intensity of the electromagnetic field at the graphene is locally enhanced;

[0010] By controlling the thickness of the double-layer film composed of aluminum oxide film and titanium dioxide film deposited on the side-polished single-crystalline organic metal perovskite optical fiber transferred with a single layer of graphene, the local enhancement effect of the electromagnetic field at the graphene is regulated.

[0011] As a preferred technical solution, the side-polished single-crystalline organic metal perovskite optical fiber includes a silica cladding and a single-crystalline organic metal perovskite core, the single-crystalline organic metal perovskite core is wrapped in the silica cladding, part of the single-crystalline organic metal perovskite core is exposed outside the silica cladding, and the exposed part of the single-crystalline organic metal perovskite core is a polishing area, the polishing area is a planar structure, and the lower surface of the optical fiber that has not been polished is an arc structure, and the single-layer graphene film, the aluminum oxide film and the titanium dioxide film are sequentially covered on the polishing area.

[0012] As a preferred technical solution, the diameter of the single crystal organic metal perovskite core is 10 to 300 μm, and / or the thickness of the silicon dioxide cladding is 10 to 200 μm.

[0013] As a preferred technical solution, the thickness of the aluminum oxide film is 0 to 50 nm.

[0014] As a preferred technical solution, the thickness of the titanium dioxide film is 160 to 200 nm.

[0015] As a preferred technical solution, the longest distance from the polished upper surface of the side-polished single-crystalline organic metal perovskite optical fiber to its unpolished lower surface is the residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber, and the residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber is 20% to 70% of the fiber diameter when it is not polished.

[0016] As a preferred technical solution, the refractive index of the titanium dioxide film is greater than the refractive index of the single crystal organic metal perovskite core.

[0017] The present invention also provides a method for preparing an electromagnetic field local enhancement structure based on a double-layer film and a side-polished perovskite optical fiber, comprising the following steps:

[0018] preparing side-polished single-crystalline organic metal perovskite optical fibers, polishing one side of the optical fiber by a wheel polishing method or a V-groove assisted polishing method, so that part of the single-crystalline organic metal perovskite fiber core is exposed to the air, cleaning impurities with an alcohol solution after the optical fiber is polished, and performing a surface passivation treatment with an isopropanol solution, so as to prepare side-polished single-crystalline organic metal perovskite optical fibers with different residual thicknesses;

[0019] Transferring a single-layer graphene film onto the polished surface of the prepared side-polished single-crystalline organic metal perovskite optical fiber;

[0020] Depositing an aluminum oxide film onto a polished surface of a side-polished single-crystalline organic metal perovskite optical fiber covered with a single-layer graphene film;

[0021] A titanium dioxide film is coated or deposited on the polished surface of the side-polished single-crystal organic metal perovskite optical fiber covered with a single-layer graphene film and an aluminum oxide film.

[0022] As a preferred technical solution, the preparation method of the single-layer graphene film is one of a microcomputer peeling method, a chemical vapor deposition method, and a silicon carbide epitaxial growth method;

[0023] And / or the transfer method of the single-layer graphene film is one of a direct growth method, a polymethyl methacrylate film-assisted wet transfer method, and a polydimethylsiloxane film-assisted dry transfer method.

[0024] As a preferred technical solution, the preparation method of the aluminum oxide film is one of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition, atomic layer deposition, and sol-gel method;

[0025] And / or the preparation method of the titanium dioxide film is one of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, atomic layer deposition technology, and sol-gel method.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] The preparation method of the invention is simple and convenient, and the structure is compact. The local field enhancement in the near-infrared band can be achieved by adopting a micron-level optical fiber polishing length. The method of realizing efficient interaction between the optical fiber mode and the single-layer graphene in the side-polished single-crystalline organic metal perovskite optical fiber by using an aluminum oxide (Al2O3) / titanium dioxide (TiO2) double-layer film structure with successively increasing refractive indices is used to realize the local enhancement of the electromagnetic field at the graphene. By controlling the thickness of the aluminum oxide (Al2O3) / titanium dioxide (TiO2) double-layer film deposited on the side-polished single-crystalline organic metal perovskite optical fiber with the transferred single-layer graphene, the local enhancement effect of the electromagnetic field at the graphene is regulated, and an effective solution is provided for improving the light absorption coefficient of the single-layer graphene. Moreover, as titanium dioxide is a humidity sensitive material, the structure provides a supporting basis for realizing high-sensitivity optical fiber humidity sensing and photoelectric detection on the perovskite optical fiber, and can be extended to other two-dimensional materials except graphene, so as to realize high-performance perovskite optical fiber integrated devices that meet the development trend of multifunctionalization and miniaturization, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a cross-sectional schematic diagram of the electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber of the present invention;

[0029] Figure 2 This is a comparison diagram of the optical field distribution of the present invention under the same optical fiber residual thickness and different device structures;

[0030] Figure 3 It is a normalized light field intensity diagram along the middle white dotted line of the light field distribution of the present invention under the same optical fiber residual thickness and different device structures;

[0031] Figure 4 It is a schematic diagram showing the effect of the thickness of the double-layer hybrid film of the present invention on the imaginary part of the effective refractive index of the TM mode;

[0032] Figure 5It is a schematic diagram for comparing the field local distribution of the present invention under the same optical fiber residual thickness and different titanium dioxide film thicknesses.

[0033] Among them, 1-silicon dioxide cladding, 2-single crystal organic metal perovskite core, 3-single layer graphene film, 4-aluminum oxide film, 5-titanium dioxide film. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Some components in the accompanying drawings are omitted, enlarged or reduced, and do not represent the actual device size. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] Example 1

[0036] like Figure 1 As shown, this embodiment provides an electromagnetic field local enhancement structure based on a double-layer film and a side-polished perovskite fiber, including: a side-polished single-crystal organic metal perovskite fiber, a single-layer graphene film 3, an aluminum oxide (Al2O3) film 4, and a titanium dioxide (TiO2) film 5 arranged in sequence from bottom to top;

[0037] The side-polished single-crystal organic metal perovskite optical fiber includes a silica cladding 1 and a single-crystal organic metal perovskite core 2. The core is made of single-crystal organic metal perovskite (MAPbBr3), and the core diameter is 10 to 300 μm, preferably 100 μm. The cladding thickness of the silica cladding 1 in this embodiment is 10 to 200 μm, preferably 20 μm. Of course, the cladding material can also be tetrafluoroethylene (C2F4). The single-crystal organic metal perovskite core 2 is wrapped in the cladding, and part of the single-crystal organic metal perovskite core 2 is exposed in the silica cladding. 1, and the exposed part of the fiber core is the polishing area, which is upward and flat, and the lower surface that has not been polished is an arc structure. The cross-section of the entire side-polished single-crystalline organic metal perovskite fiber is similar to a "D" shape placed on its side, and the longest distance from the polishing area to its lower surface is the remaining thickness of the side-polished perovskite fiber; the single-layer graphene film 3, the aluminum oxide film 4 and the titanium dioxide film 5 are tightly covered on the polishing area where the fiber core is exposed in sequence; after the perovskite fiber is polished, the evanescent field leaks from the polishing area of ​​the fiber, and under the action of the aluminum oxide / titanium dioxide double-layer film, the light field is attracted to the vicinity of the single-layer graphene and absorbed by the graphene.

[0038] In this embodiment, the preparation method of the single-layer graphene film is one of a microcomputer peeling method, a chemical vapor deposition method (CVD), and a silicon carbide epitaxial growth method; the transfer method of the single-layer graphene film is one of a direct growth method, a polymethyl methacrylate (PMMA) film-assisted wet transfer method, and a polydimethylsiloxane (PDMS) film-assisted dry transfer method;

[0039] Specifically, the microcomputer exfoliation method is used as an example to illustrate that the graphene prepared by this method has the characteristics of high quality, no chemical pollution, and few defects. The specific steps are as follows:

[0040] (1) taking a piece of high-quality graphite crystal grown by chemical vapor deposition, placing it in an inert gas environment for 30 minutes to pre-treat the graphite crystal, tearing off a small piece of graphite crystal with 3M tape, taking another piece of clean 3M tape and laminating it with the 3M tape with the small piece of graphite crystal, and quickly tearing it apart, repeating this step for more than 5 times to obtain a single-layer, few-layer or even multi-layer graphene nanosheet;

[0041] (2) Using a 500 μm thick medium-adhesive polydimethylsiloxane (PDMS) film to stick the graphene nanosheets from the 3M tape, and observe them under a microscope to find large-area, flat single-layer graphene nanosheets;

[0042] (3) Using a two-dimensional material transfer platform, high-quality single-layer graphene nanosheets are transferred to the polishing area of ​​the side-polished single-crystalline organic metal perovskite optical fiber. The heating function of the two-dimensional material transfer platform is activated, the temperature is set to 80°C, and the heating time is 10 minutes to make the PDMS film lose its viscosity. The PDMS film is removed to complete the release of the single-layer graphene nanosheet, and the transfer is completed.

[0043] In this embodiment, the preparation method of the aluminum oxide film is one of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition, atomic layer deposition, and sol-gel method, and the thickness of the aluminum oxide film is 0 to 50 nm;

[0044] In this embodiment, the titanium dioxide film is prepared by a method of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, atomic layer deposition, or sol-gel method, and the thickness of the titanium dioxide film is 160 to 200 nm.

[0045] In this embodiment, the refractive index of the titanium dioxide film at a wavelength of 1600nm is 2.4299+0.0001, and the refractive index of the single-crystalline organic metal perovskite fiber core at a wavelength of 1600nm is 1.9841+0.02068i. It can be seen that the real part of the refractive index of the titanium dioxide film is greater than the real part of the refractive index of the single-crystalline organic metal perovskite fiber core, and the refractive index distribution satisfies the condition that light is always transmitted in a medium with a large refractive index.

[0046] In this embodiment, the polished upper surface of the side-polished single-crystalline organic metal perovskite optical fiber is a planar structure, the length of the polished area is 5 to 5000 μm, the unpolished lower surface of the side-polished single-crystalline organic metal perovskite optical fiber is an arc-shaped structure, and the longest distance from the polished upper surface of the side-polished single-crystalline organic metal perovskite optical fiber to its unpolished lower surface is the residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber. The residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber is 20% to 70% of the fiber diameter when it is not polished. This embodiment is described by taking the side-polished single-crystalline organic metal perovskite optical fiber with a residual thickness of 65 μm and 70 μm as an example;

[0047] In this embodiment, a wheel polishing method is used to polish away part of the single-crystalline organic metal perovskite core 2 and the silica cladding 1 to obtain a side-polished single-crystalline organic metal perovskite optical fiber; a microcomputer stripping method is used to strip the graphite crystal to obtain a single-layer graphene, and a 500 μm thick medium-viscosity polydimethylsiloxane (PDMS) film is used to transfer the single-layer graphene to the top of the polishing area by a thermal release method (temperature setting 80°C, heating time 10 minutes). Dry transfer can avoid the influence of chemical residues on the optical and electrical properties of graphene, reduce defects, and improve the quality of graphene transfer. Then, a vacuum resistance heating evaporation method is used to deposit an aluminum oxide film and a titanium dioxide film in sequence on the polishing area.

[0048] Specifically, the preparation process is:

[0049] Step 1: Preparation of side-polished single-crystalline organic metal perovskite optical fiber: polish one side of a section of grown single-crystalline organic metal perovskite optical fiber by a wheel polishing method or a V-groove assisted polishing method, remove part of the optical fiber cladding and core so that the single-crystalline organic metal perovskite core is exposed to the air, clean the impurities with an alcohol solution after polishing the optical fiber, and perform surface passivation treatment with an isopropanol solution to reduce surface defects, thereby preparing side-polished single-crystalline organic metal perovskite optical fibers with different residual thicknesses;

[0050] Step 2: Transferring the single-layer graphene film onto the polished surface of the side-polished single-crystalline organic metal perovskite optical fiber prepared in step 1;

[0051] Step 3: depositing a high-quality aluminum oxide film onto the polished surface of the side-polished single-crystalline organic metal perovskite optical fiber covered with a single-layer graphene film obtained in step 2;

[0052] Step 4: coating or depositing a high-quality titanium dioxide film onto the polished surface of the side-polished single-crystalline organic metal perovskite optical fiber covered with a single-layer graphene film and an aluminum oxide film obtained in step 3.

[0053] like Figure 2 and Figure 3 As shown, the Comsol finite element analysis method is used to establish the above model structure and perform simulation analysis. Since the refractive index of single-crystalline organic metal perovskite is much larger than that of single-layer graphene, the simulation confirms that the light field distribution of the side-polished single-crystalline organic metal perovskite optical fiber is mainly concentrated in the fiber core. After covering the single-layer graphene, the light field of the optical fiber is still concentrated in the fiber core. At this time, the evanescent field leaked from the polished area of ​​the optical fiber interacts with the graphene, and the interaction intensity is weak, making it difficult to achieve highly sensitive photoelectric detection and sensing. After depositing the aluminum oxide / titanium dioxide double-layer film, the high-refractive-index double-layer film attracts the light field originally in the fiber core to the vicinity of the graphene, and the local field intensity at the graphene is greatly enhanced. At this time, the optical fiber TM mode is efficiently coupled with the graphene, and the light-material interaction intensity and the light absorption coefficient are greatly enhanced.

[0054] like Figure 4 As shown, it shows the effect of the thickness of the Al2O3 film and the TiO2 film on the imaginary part of the effective refractive index of the TM mode under the condition that the residual thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, where the maximum thickness of the Al2O3 film is 50nm, and the maximum thickness of the TiO2 film is 200nm. Figure 4 The size of the solid dots represents the size of the imaginary part of the effective refractive index of the TM mode, and the maximum imaginary part value is 0.020302 (@10nm Al2O3 and 170nm TiO2). Figure 4 As shown by the solid circles, under the local field enhancement conditions of the TM mode, the thickness of the titanium dioxide film increases with the increase of the thickness of the aluminum oxide film. The results show that double-layer films with different thickness ratios can achieve different degrees of light absorption. Therefore, the local enhancement effect of the electromagnetic field near the single-layer graphene can be controlled by designing the thickness of the double-layer film.

[0055] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thickness of the aluminum oxide film and the titanium dioxide film on the single-layer graphene film are 5nm and 170nm respectively, and the refractive index at a wavelength of 1600nm is 1.6139 and 2.4299+0.0001 respectively. By utilizing the Al2O3 / TiO2 double-layer film with a gradually increasing refractive index, the light field originally concentrated in the middle of the fiber core can be attracted to the vicinity of the graphene layer in the TM mode. At this time, the electromagnetic field size at the graphene position is enhanced from the original 33.33V / m to 812.7V / m, and the interaction strength (i.e., the electromagnetic field strength corresponding to the position of the graphene layer) is enhanced by 24.38 times. The light absorption coefficient under this structure reaches 0.67dB / μm.

[0056] More specifically, the light absorption coefficient α is calculated by formula 1-1:

[0057]

[0058] Where λ is the wavelength of the incident light, Im(n eff ) is the imaginary part of the mode effective refractive index.

[0059] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thicknesses of the aluminum oxide film and the titanium dioxide film are 10nm and 170nm respectively, and the refractive indices at a wavelength of 1600nm are 1.6139 and 2.4299+0.0001 respectively. By utilizing the double-layer Al2O3 / TiO2 hybrid film with a gradually increasing refractive index, the light field originally concentrated in the middle of the fiber core can be attracted to the vicinity of the graphene layer in the TM mode. At this time, the electromagnetic field size at the graphene position is enhanced from the original 33.33V / m to 835.73V / m, and the interaction strength is enhanced by 25.07 times. The light absorption coefficient under this structure reaches 0.69dB / μm, and the interaction length at the micron level can achieve efficient light absorption of a single-layer graphene.

[0060] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thicknesses of the aluminum oxide film and the titanium dioxide film are 20nm and 180nm respectively, and the refractive indices at a wavelength of 1600nm are 1.6139 and 2.4299+0.0001 respectively. By utilizing the Al2O3 / TiO2 double-layer film with a gradually increasing refractive index, the light field originally concentrated in the middle of the fiber core can be attracted to the vicinity of the graphene layer in the TM mode. At this time, the electromagnetic field size at the graphene position is enhanced from the original 33.33V / m to 776.94V / m, and the interaction strength is enhanced by 23.31 times. The light absorption coefficient under this structure reaches 0.66dB / μm.

[0061] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thicknesses of the aluminum oxide film and the titanium dioxide film are 40nm and 190nm respectively, and by utilizing the Al2O3 / TiO2 double-layer film with a gradually increasing refractive index, the light field originally concentrated in the middle of the fiber core can be attracted to the vicinity of the graphene layer in the TM mode, thereby enhancing the field intensity at the graphene layer by 22.72 times.

[0062] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 70μm, the thicknesses of the aluminum oxide film and the titanium dioxide film are 10nm and 170nm respectively, and the refractive indices at a wavelength of 1600nm are 1.6139 and 2.4299+0.0001 respectively. At this time, the electromagnetic field size at the graphene position is enhanced from the original 29.26V / m to 761V / m, and the interaction strength is enhanced by 26 times. The light absorption coefficient under this structure reaches 0.692dB / μm.

[0063] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 70μm, the thicknesses of the aluminum oxide film and the titanium dioxide film are 40nm and 190nm respectively, and the refractive indices at a wavelength of 1600nm are 1.6139 and 2.4299+0.0001 respectively. At this time, the electromagnetic field size at the graphene position is enhanced from the original 29.26V / m to 731.8V / m, and the interaction strength is enhanced by 25.01 times. The light absorption coefficient under this structure reaches 0.68dB / μm.

[0064] Preferably, when the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 70 μm, and the thickness of the aluminum oxide film and the titanium dioxide film are 10 nm and 170 nm respectively, the local enhancement effect of the electromagnetic field is optimal. In addition, the device structure is sensitive to external refractive index changes, and its sensitivity can reach 27.77 dB / RIU when the effective coverage length of the device is 100 μm.

[0065] In this embodiment, the TiO2 film attracts the light field in the optical fiber to the vicinity of the TiO2 film, and the 10nm Al2O3 film acts as a reflective film to increase the back and forth reflection of the light field between the Al2O3 film and the optical fiber, so that obvious local enhancement of the electromagnetic field appears near the single-layer graphene. In addition, the local enhancement effect of the electromagnetic field near the single-layer graphene can be controlled by optimizing the design of the remaining thickness of the optical fiber and the thickness ratio of the Al2O3 / TiO2 double-layer film.

[0066] The manufacturing method of the present invention is simple and compact, and the local field enhancement in the near-infrared band can be achieved by using a micron-level optical fiber polishing length. The technical method of the present invention can be extended to other two-dimensional materials besides graphene, and realize high-performance perovskite optical fiber integrated devices that meet the development trend of multifunctionalization and miniaturization, and has broad application prospects.

[0067] Example 2

[0068] This embodiment discloses an electromagnetic field local enhancement structure based on titanium dioxide film and side-polished perovskite fiber, comprising: arranged in sequence from bottom to top: a side-polished single-crystalline organic metal perovskite fiber, a single-layer graphene film, and a titanium dioxide film, wherein the side-polished single-crystalline organic metal perovskite fiber comprises a silicon dioxide cladding and a single-crystalline organic metal perovskite core. The difference between Embodiment 2 and Embodiment 1 is that Embodiment 2 is a field enhancement structure based on a single-layer titanium dioxide film, and Embodiment 1 is a field enhancement structure based on a double-layer aluminum oxide / titanium dioxide film.

[0069] Specifically, the core diameter of the single-crystalline organic metal perovskite optical fiber is 100 μm, the thickness of the silica cladding is 20 μm, and a wheel polishing method is used to polish off half of the core and cladding to obtain a side-polished single-crystalline organic metal perovskite optical fiber with a remaining thickness of 65 μm; a microcomputer stripping method is used to strip the graphite crystal to obtain a single-layer graphene, and a 500 μm thick medium-viscosity polydimethylsiloxane (PDMS) film is used to transfer the single-layer graphene to the top of the polishing area using a thermal release method (temperature setting 80°C, heating time 10 minutes). Dry transfer can avoid the influence of chemical residues on the optical and electrical properties of graphene, reduce defects, and improve the quality of graphene transfer; then a vacuum resistance heating evaporation method is used to deposit a titanium dioxide film on the polishing area.

[0070] like Figure 5 As shown, the Comsol finite element analysis method was used to establish the above model structure. The simulation confirmed that with the increase of the thickness of the titanium dioxide film, the light field transmitted in the fiber core gradually concentrated near the polished surface, and by optimizing the thickness of the titanium dioxide film, the interaction strength between light and graphene can be optimized.

[0071] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thickness of the titanium dioxide film deposited on the single-layer graphene film is 160nm, and the refractive index at a wavelength of 1600nm is 2.4299+0.0001. At this time, the light field distribution in the fiber core gradually concentrates near the polished surface, and the electromagnetic field size at the graphene position is enhanced from the original 33.33V / m to 470V / m, and the interaction intensity (that is, the field strength corresponding to the graphene layer position) is enhanced by 14.1 times.

[0072] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65μm, the thickness of the titanium dioxide film deposited on the single-layer graphene film is 170nm, and the refractive index at a wavelength of 1600nm is 2.4299+0.0001. At this time, the optical fiber TM mode is efficiently coupled with the graphene, and the electromagnetic field is localized near the position of the graphene. The electromagnetic field size is enhanced from the original 33.33V / m to 829.5V / m, and the interaction strength is enhanced by 24.89 times, realizing efficient interaction between the optical fiber mode and the single-layer graphene.

[0073] Specifically, the remaining thickness of the side-polished single-crystal organic metal perovskite optical fiber is 65 μm, the thickness of the titanium dioxide film deposited on the single-layer graphene film is 180 nm, and the refractive index at a wavelength of 1600 nm is 2.4299+0.0001. At this time, the field intensity at the graphene position is periodically enhanced, and the electromagnetic field size at the graphene position is enhanced from the original 33.33 V / m to a maximum of 64.4 V / m, and the interaction strength is enhanced by 1.93 times;

[0074] Preferably, in a device structure in which a single-layer titanium dioxide film enhances the interaction between graphene and side-polished perovskite optical fiber, when the remaining thickness of the optical fiber is 65 μm and the thickness of the titanium dioxide film is 170 nm, the field local enhancement effect near the graphene is optimal.

[0075] According to the above-mentioned Example 1 and Example 2, under the same residual thickness of the optical fiber and the same thickness of the titanium dioxide film, 10nm of aluminum oxide is evaporated before evaporating the titanium dioxide film, which can enhance the reflection of light in the aluminum oxide and the fiber core and further enhance the field localization effect.

[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite fiber, characterized in that: include: Side-polished single-crystal organometallic perovskite optical fiber, single-layer graphene film, aluminum oxide film and titanium dioxide film; The single-layer graphene film, the aluminum oxide film and the titanium dioxide film are disposed layer by layer on the polished surface of the side-polished single-crystal organic metal perovskite optical fiber; Based on the double-layer film structure composed of aluminum oxide film and titanium dioxide film with increasing refractive index, the interaction between the fiber mode and the single-layer graphene in the side-polished single-crystal organic metal perovskite fiber is realized, and the intensity of the electromagnetic field at the graphene is locally enhanced; By controlling the thickness of the double-layer film composed of aluminum oxide film and titanium dioxide film deposited on the side-polished single-crystalline organic metal perovskite optical fiber transferred with a single layer of graphene, the local enhancement effect of the electromagnetic field at the graphene is regulated.

2. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 1, characterized in that: The side-polished single-crystalline organic metal perovskite optical fiber includes a silica cladding and a single-crystalline organic metal perovskite core, the single-crystalline organic metal perovskite core is wrapped in the silica cladding, part of the single-crystalline organic metal perovskite core is exposed outside the silica cladding, and the exposed part of the single-crystalline organic metal perovskite core is a polishing area, the polishing area is a planar structure, and the lower surface of the optical fiber that has not been polished is an arc structure, and the single-layer graphene film, the aluminum oxide film and the titanium dioxide film are sequentially covered on the polishing area.

3. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 2, characterized in that: The diameter of the single crystal organic metal perovskite core is 10 to 300 μm, and the thickness of the silicon dioxide cladding is 10 to 200 μm.

4. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 1, characterized in that: The thickness of the aluminum oxide film is 0 to 50 nm.

5. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 1, characterized in that: The thickness of the titanium dioxide film is 160 to 200 nm.

6. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 1, characterized in that: The longest distance from the polished upper surface to the unpolished lower surface of the side-polished single-crystalline organic metal perovskite optical fiber is the residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber, and the residual thickness of the side-polished single-crystalline organic metal perovskite optical fiber is 20% to 70% of the unpolished optical fiber diameter.

7. The electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 1, characterized in that: The refractive index of the titanium dioxide film is greater than the refractive index of the single crystal organic metal perovskite fiber core.

8. The method for preparing an electromagnetic field local enhancement structure based on a double-layer film and side-polished perovskite optical fiber according to any one of claims 1 to 7, characterized in that: The steps include: preparing side-polished single-crystalline organic metal perovskite optical fibers, polishing one side of the optical fiber by a wheel polishing method or a V-groove assisted polishing method, so that part of the single-crystalline organic metal perovskite fiber core is exposed to the air, cleaning impurities with an alcohol solution after the optical fiber is polished, and performing a surface passivation treatment with an isopropanol solution, so as to prepare side-polished single-crystalline organic metal perovskite optical fibers with different residual thicknesses; Transferring a single-layer graphene film onto the polished surface of the prepared side-polished single-crystalline organic metal perovskite optical fiber; Depositing an aluminum oxide film onto a polished surface of a side-polished single-crystalline organic metal perovskite optical fiber covered with a single-layer graphene film; A titanium dioxide film is coated or deposited on the polished surface of the side-polished single-crystal organic metal perovskite optical fiber covered with a single-layer graphene film and an aluminum oxide film.

9. The method for preparing the electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 8, characterized in that: The preparation method of the single-layer graphene film is one of a microcomputer exfoliation method, a chemical vapor deposition method, and a silicon carbide epitaxial growth method; And / or the transfer method of the single-layer graphene film is one of a direct growth method, a polymethyl methacrylate film-assisted wet transfer method, and a polydimethylsiloxane film-assisted dry transfer method.

10. The method for preparing the electromagnetic field local enhancement structure based on double-layer film and side-polished perovskite optical fiber according to claim 8, characterized in that: The preparation method of the aluminum oxide film is one of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition, atomic layer deposition, and sol-gel method; And / or the preparation method of the titanium dioxide film is one of vacuum resistance heating evaporation, electron beam evaporation, magnetron sputtering deposition, pulsed laser deposition, chemical vapor deposition, atomic layer deposition technology, and sol-gel method.

Citation Information

Patent Citations

  • Optical fiber integrated photoelectric detector with polarization function

    CN113865702A

  • Graphene composite electrode material

    CN107819123A

  • Side is thrown and is polished fibre and sensor thereof

    CN204584944U

  • Integrated graphite alkene photoelectric detector of optic fibre

    CN208333670U

  • Refractive index sensor based on multilateral polishing optical fiber surface plasma resonance

    CN215866382U